Cross-generational ripples: sublethal fipronil exposure alters Binodoxys communis microbiome without lethal consequences - Wang, Lisha; Liu, Weijiao; Wang, Li; Zhang, Kaixin; Li, Dongyang; Ji, Jichao; Luo, Junyu; Zhu, Xiangzhen; Cui, Jinjie; Gao, Xueke (Frontiers in Microbiology, 2025)
IntroductionFipronil, a broad-spectrum phenylpyrazole insecticide, demonstrates high efficacy against Aphis gossypii (cotton aphid). However, its potential effects on Binodoxys communis, a key natural enemy of A. gossypii, remain largely unexplored. This study comprehensively assessed the safety of fipronil for B. communis, with particular emphasis on sublethal effects and associated microbiome alterations.MethodsWe evaluated the sublethal effects of fipronil on the development of B. communis across parental (F0) and offspring (F1) generations. Furthermore, the alterations in the microbial diversity and community structure of B. communis were analyzed using 16S rRNA sequencing. Functional prediction of the microbiota was performed via PICRUSt2.ResultsIndirect fipronil exposure significantly prolonged larval development in the parental generation (F0, p = 0.017), while showing no statistically significant impact on the offspring generation (F1). 16S rRNA sequencing revealed apparent alterations in the microbial community. In adults, the dominant genus shifted from Akkermansia to Muribaculum after 1 h exposure, while the dominant phylum showed significantly reduced abundance after 3 d. In larvae, the major phylum (Proteobacteria) remained unchanged, but the major genus shifted from Brevitalea to Vicinamibacter. Functional prediction indicated that the predicted genes were predominantly enriched in metabolic pathways (75% of the functional repertoire).DiscussionThese results suggest that fipronil exposure induces previously unrecognized sublethal effects on a key natural enemy insect, primarily by disrupting its symbiotic microbiota, which may play a major role in host metabolism. Our findings highlight the ecological risks of fipronil and emphasize the need for pesticide risk assessments that consider sublethal effects on beneficial insects and their microbiota.